Histopathological Spectrum of Myocardial Fibrosis and its Association with Cardiac Autonomic Function in Ischemic Heart Disease, with Implications in Critical Care and Pulmonary Dysfunction - Abdul Rauf, Muhammad Omair Zahid, Dur-E-Shehwar Ali, Muhammad Ali, Sana Jawad, Saima Jatoi (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Myocardial fibrosis is a common pathological consequence of ischemic heart disease (IHD) and contributes to adverse cardiac remodeling, impaired autonomic regulation, and cardiopulmonary dysfunction. Structural changes caused by fibrosis disrupt myocardial architecture and electrical conduction pathways, which may lead to autonomic imbalance and respiratory complications, particularly in critically ill patients. Objective: To evaluate the histopathological spectrum of myocardial fibrosis and its association with cardiac autonomic function in patients with ischemic heart disease, along with its implications for pulmonary dysfunction and critical care management. Methods: This cross-sectional observational study was conducted at Mayo Hospital, Lahore, Pakistan, and Isra University Hospital, Hyderabad, Pakistan, from May 2022 to May 2023. A total of 100 patients with ischemic heart disease were included. Myocardial tissue samples obtained during surgical procedures or autopsy were examined using hematoxylin–eosin and Masson’s trichrome staining to identify patterns of fibrosis. Cardiac autonomic function was assessed through heart rate variability (HRV) analysis and autonomic reflex tests. Pulmonary function was evaluated using arterial blood gas analysis, pulse oximetry, and spirometry. Results: Histopathological analysis showed that interstitial fibrosis was the most common pattern (45%), followed by replacement fibrosis (30%), perivascular fibrosis (15%), and diffuse fibrosis (10%). Moderate to severe myocardial fibrosis was identified in the majority of patients. Individuals with severe fibrosis demonstrated significantly reduced HRV parameters, indicating marked autonomic dysfunction. Furthermore, patients with advanced fibrosis exhibited lower oxygen saturation, reduced PaO₂ levels, and impaired spirometric values, suggesting associated pulmonary dysfunction. Conclusion: Myocardial fibrosis plays a critical role in structural cardiac remodeling in ischemic heart disease and is significantly associated with cardiac autonomic dysfunction and pulmonary impairment. Early recognition of myocardial fibrosis may improve risk stratification and guide management strategies in cardiology and critical care settings. Keywords: Myocardial fibrosis, ischemic heart disease, cardiac autonomic dysfunction, pulmonary dysfunction, histopathology, critical care medicine.